Preservation of Antigen-Specific Functions of αβ T Cells and B Cells Removed from Hematopoietic Stem Cell Transplants Suggests Their Use As an Alternative Cell Source for Advanced Manipulation and Adoptive Immunotherapy - Li Pira, Giuseppina; Di Cecca, Stefano; Biagini, Simone; Girolami, Elia; Cicchetti, Elisabetta; Bertaina, Valentina; Quintarelli, Concetta; Caruana, Ignazio; Lucarelli, Barbarella; Merli, Pietro; Pagliara, Daria; Brescia, Letizia Pomponia; et al. (Frontiers in Immunology, 2017)
Hematopoietic stem cell transplantation (HSCT) is standard therapy for numerous hematological diseases. The use of haploidentical donors, sharing half of the HLA alleles with the recipient, has facilitated the use of this procedure as patients can rely on availability of a haploidentical donor within their family. Since HLA disparity increases the risk of graft-versus-host disease, T-cell depletion has been used to remove alloreactive lymphocytes from the graft. Selective removal of αβ T cells, which encompass the alloreactive repertoire, combined with removal of B cells to prevent EBV-related lymphoproliferative disease, proved safe and effective in clinical studies. Depleted αβ T cells and B cells are generally discarded as by-products. Considering the possible use of donor T cells for donor lymphocyte infusions or for generation of pathogen-specific T cells as mediators of graft-versus-infection (GvI) effect, we tested whether cells in the discarded fractions were functionally intact. Response to alloantigens and to viral antigens comparable to that of unmanipulated cells indicated a functional integrity of αβ T cells, in spite of the manipulation used for their depletion. Furthermore, B cells proved to be efficient antigen-presenting cells, indicating that antigen uptake, processing and presentation were fully preserved. Therefore, we propose that separated αβ T lymphocytes could be employed for obtaining pathogen-specific T cells, applying available methods for positive selection, which eventually leads to indirect allodepletion. In addition, these functional T cells could undergo additional manipulation, such as direct allodepletion or genetic modification.